Igrzyska gladiatorskie - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2011)
Recenzja książki: Lyudmil F. Vagalinski, Kryv i zrelišta. Sportni i gladiatorski igri w elinističeska i rimska Trakija, Blood and Entertainments. Sports and Gladiatorial Games in Hellenistic and Roman Thrace, Bulgarian Academy of Sciences, National Archaeological Institute with Museum Sofia, Sofia 2009, 238 s., ilustracje